2013
DOI: 10.1186/1479-5868-10-128
|View full text |Cite
|
Sign up to set email alerts
|

Association between community garden participation and fruit and vegetable consumption in rural Missouri

Abstract: BackgroundFruit and vegetable consumption reduces chronic disease risk, yet the majority of Americans consume fewer than recommended. Inadequate access to fruits and vegetables is increasingly recognized as a significant contributor to low consumption of healthy foods. Emerging evidence shows the effectiveness of community gardens in increasing access to, and consumption of, fruits and vegetables.MethodsTwo complementary studies explored the association of community garden participation and fruit and vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 20 publications
8
75
0
1
Order By: Relevance
“…For children, there is evidence to suggest that engagement with food and exposure to the process of harvesting and production has a positive impact on willingness to eat a wider range of vegetables . Projects that involve children and adults in growing food appear to have a positive effect on consumption, especially where there is an element of food preparation . These results highlight the value of community‐driven interventions, and the importance of continued investment by government and health promotion practitioners to strengthen community action.…”
Section: Implications For Health Promotionmentioning
confidence: 99%
“…For children, there is evidence to suggest that engagement with food and exposure to the process of harvesting and production has a positive impact on willingness to eat a wider range of vegetables . Projects that involve children and adults in growing food appear to have a positive effect on consumption, especially where there is an element of food preparation . These results highlight the value of community‐driven interventions, and the importance of continued investment by government and health promotion practitioners to strengthen community action.…”
Section: Implications For Health Promotionmentioning
confidence: 99%
“…Through their involvement in growing and sharing food, participants reported higher levels of household fruit and vegetable consumption. This has also been reported by Noy et al and Barnidge et al . Programs like MH can therefore be said to have contributed to improving food and nutrition security, defined as adequate access to safe, nutritious and socially acceptable food .…”
Section: Discussionmentioning
confidence: 99%
“…Lackey ( 1998 ) found that community garden participants were more likely to agree that they had eaten a balanced diet in previous months (fruits/vegetables, breads/cereals, meat/fi sh/beans, and dairy) than non-gardeners. Barnidge et al ( 2013 ) found that in addition to a perceived increase in fruit and vegetable consumption, more frequent community garden participation was also associated with reporting eating fresher produce, being able to provide for themselves and their family, and eating less fast food. Further, vegetables and fruits can lose nutritive value with increased storage time and temperature.…”
mentioning
confidence: 93%
“…They found that individuals who worked in a community garden at least once a week were more likely to report eating fruits and vegetables because of their community garden work. Further, the 5 % of residents that reported community garden participation were more likely to report eating fruits two or more times per day and vegetables three or more times per day than those who did not report community garden participation, after adjusting for covariates (Barnidge et al 2013 ).…”
mentioning
confidence: 96%
See 1 more Smart Citation